Upaya Meningkatkan Prestasi Belajar Siswa Dengan Menggunakan Media Gambar Pada Mata Pelajaran IPS di Madrasah Ibtidaiyah - Muhammad Saipul Watoni (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2017)
Teacher as a main component in fixing the successes of expected instructional activity to choose and use the good instructional method in delivering learning material. Nowadays, the instructional activity of IPS is still centered on teacher and characterized classical, so the teacher’s role more than students. So that the instructional model which can invite students to be active is needed. One of the instructional method which can increase learning activity is using picture media. The picture media is the whole things manifested visually into two dimension form as outpouring or thinking like pot ret, slide, and strip. The aim of this research is to know the use of visual picture media in increasing the student’s learning achievement of subject matter of IPS SD/MI. The type of this research is classroom action research (PTK) and the research sample is IV MI NW Keruak, the number of subjects is 25 students. To measure the level of understanding and activity of students used the instrument, the instrument used is a questionnaire-shaped observation and multiple-choice test consisting of 10 items about the cycle. Based on the results of data analysis obtained value in the first cycle reached 52.29% with an average of 61.86. Second Cycle reaches 87.08% with average 77.52 average (77.53> 61.88) this means that the use of learning picture media can improve student achievement in fourth grade students of MI NW Keruak